A Demarcation Full of Tension - Mette Volquartzen; Rasmus Dahlberg (Nordic Journal of Studies in Policing)
This article, partly based on declassified police and military documents, investigates how military support for the police in Danish domestic security affairs has undergone a recategorization process. We investigate and evaluate the legitimization process that has occurred, focusing on cases that cross the ideological and symbolic demarcation between the police and military, and the accompanying tensions surrounding that demarcation. To do so, we utilize Beetham’s (2013) three legitimizing components: conformity to rules, justifiability of rules in terms of shared beliefs, and legitimation through expressed consent, assessing the level of legitimacy in five consecutive periods (1968–1979, 1980–1989, 1990–2000, 2001–2014, and 2015–2018). We conclude that our evidence supports the expectation that Danish police-military cooperation has undergone a transformative legitimization process between 1968 and 2018, which has led to the acknowledgment of the extension of powers to persons or institutions to whom they were not previously granted.